Effectiveness of Ageratum conyzoides (Babandotan) Leaf Extract and Sapindus rarak (Lerak) Fruit Extract in Control of Myzus persicae in Chili Plants - Djamilah Djamilah; Umm Ro'ina Rosyda; Yudhi Harini Bertham (Badan Penerbitan Fakultas Pertanian (BPFP), 2021)
Chili is one of the important agricultural commodities in Indonesia. Myzus persicae Sulz. is one of the important pests in Chili cultivation because it can cause damage up to 80%. Nabati insecticide utilization is one of the safer alternatives to control and more environmentally friendly than synthetic insecticides. One Nabati insecticide utilization that can be used in controlling pests are Ageratum conyzoides L extract and Sapindus rarak D.C extract . The purpose of this study was to determine the effectiveness of A. Conyzoides extract S. rarak extracts and extract S. rarak mixture of both in the control of M. persicae. This research was factorial, treatment consisted of 2 factors: 1 Nabati insecticide consists of A. Conyzoides and S. Rarak and factor of 2 each given concentration is 0 ml, 10 ml, 20 ml, 30 ml. Using a completely randomized design (CRD) with 16 treatments 3 replications. The results variance showed that the treatment performed with extracts from A. conyzoides effect on mortality, damage to crops, M. persicae life, and leaf greenness level after treatment. Extract treatment S. Rarak effect on mortality, M. persicae life and leaf greenness level after treatment. While treatment mix A. conyzoides leaf extracts and fruit extracts S. rarak effect on mortality, M. persicae life. The results showed that the treatment is effective in controlling pests aphids M. persicae are A. conyzoides leaf extract mixture of 30 ml and 30 ml S. rarak fruit extract with the highest mortality value of 96.14%, which gives a real influence in the control of aphids M. persicae and different real control. LC50 and LC90 showed the best application in the control extract are 18.46 ml and 51.86 ml.